Clarifying species boundaries between bocachico (Prochilodus magdalenae) and bocachico de Maracaibo (Prochilodus reticulatus) (characiformes: Prochilodontidae) using complete mitochondrial genomes - Yepes-Blandón, Jonny; Almansa-Villa, Diego; Benítez-Galeano, María José; Mir, Daiana; Hernández-Rangel, Jim; Atencio-García, Víctor; Estrada-Posada, Ana; Rodríguez-Osorio, Nélida (Frontiers in Genetics, 2025)
The accurate phylogenetic distinction between Prochilodus magdalenae and Prochilodus reticulatus (Characiformes: Prochilodontidae) has been hindered by overlapping morphology and limited sequence data. Previous studies, relying on partial mitochondrial markers, have even suggested that Prochilodus magdalenae and Prochilodus reticulatus might be a single species. This study presents three annotated complete mitochondrial genomes for P. reticulatus and phylogenetic analyses that contribute to resolving uncertainty around these species’ boundaries. Our phylogenetic reconstructions, using both mitochondrial markers and complete mitogenomes, consistently support the segregation of P. magdalenae and P. reticulatus into distinct clades. Bayesian time-calibrated analysis estimates their divergence at approximately 6.9 mya (10.2–4.2 mya), coinciding with the Andean Eastern Cordillera’s final uplift. This study provides essential data for future taxonomic and conservation efforts. Our findings clarify the phylogenetic relationship between these species, emphasizing the utility of complete mitogenomes and demonstrating that sequence mislabeling, probably caused by the difficulty of accurately identifying these species based on morphological characteristics, has contributed to inconsistencies in previous phylogenetic studies within the genus Prochilodus.